Manufacturing performance management using SAP OEE : implementing and configuring overall equipment effectiveness /: implementing and configuring overall equipment effectiveness. (2016) - Saha, Dipankar; Syamsunder, Mahalakshmi; Chakraborty, Sumanta
No abstract available